Glomerulopatias primárias que cursam com síndrome nefrótica como importante causa de doença renal crônica: uma revisão integrativa - COSTA JUNIOR, Carlos Augusto Leão (2025)
Introduction: Chronic kidney disease (CKD) is characterized by the progressive loss of nephron function. In Brazil, considering all stages of the disease, it is estimated that there are between 3 and 6 million people with CKD. The main causes of CKD worldwide are diabetes mellitus (DM) and arterial hypertension (AH), followed by glomerulopathies. Objectives: To demonstrate the contributions of the most common glomerulopathies of nephrotic evolution to chronic kidney disease at any stage by means of an integrative literature review. Methodology: This is an integrative literature review. Articles related to children with nephrotic syndrome were excluded from the selection. Results and discussion: After reading the abstracts, 5 articles were selected for analysis and development of this review. The studies described various glomerulopathies, including segmental and focal glomerulosclerosis, minimal lesion disease, IgA glomerulopathy and membranous glomerulopathy. Conclusion: In general, the most common glomerulopathies in the studies were segmental and focal glomerulosclerosis, followed by minimal lesion disease.